Comparative manufacture and testing of induction- welded and adhesively bonded carbon fibre PEEK stiffened panels. (December 2019) - Flanagan, M; Doyle, A; Doyle, K; Ward, M; Bizeul, M; Canavan, R; Weafer, B; Ó Brádaigh, CM; Harrison, NM; Goggins, J
This work presents details of manufacturing and testing of a carbon fibre polyetheretherketone induction-welded hat-stiffened panel. Mechanical testing is carried out to evaluate the performance of the welded assembly and results are compared with similar testing of an adhesively bonded panel. The results show that the welded panel and the bonded panel had similar load-bearing capacity (<2% difference) and stiffness (<1% difference). Optical microscopy is used to verify the weld quality and identify manufacturing artefacts associated with induction welding. Inspection of the panel after welding shows that the induction welding process caused minor warpage, voids and delamination in the panel. The work addresses the lack of data relating to demonstrator scale welded assemblies in the literature, demonstrates that continuous induction welding is a suitable assembly technique for aerospace and automotive components under uniaxial in-plane compressive loading and identifies process-induced artefacts that may occur during induction welding.